Frequency and impact of enteric hyperoxaluria in pediatric short bowel syndrome: a retrospective single centre study - Schaefer, Jan Thomas; Schulz-Heise, Susanne; Rueckel, Aline; Rauh, Manfred; Juengert, Joerg; Galiano, Matthias; Meier, Norbert; Woelfle, Joachim; Schiffer, Mario; Hoerning, André (Frontiers in Pediatrics, 2023)
349 hat gelöscht: echoic 350 hat gelöscht: of 351 hat gelöscht: was not explained 352 hat gelöscht: O 353 hat gelöscht: In the follow-up study by Roberts, 32,5% 354 patients still had sonographic abnormalities 3 , although 355 additionally the sonographic picture of the individual patient 356 changed in some cases, so resulting in an interthat some of 357 the patients switchchange of patients ed between the 358 groups. 359 Kommentiert [MOU2]: Ich würde die Roberts Info shier streichen, zu komplex zu erklären.. hat gelöscht: Echogenicity abnormalities as in studies by 360 Kosar or Roberts were explicitly not investigated in the 361 present study. Since the grading and reproducibility of these 362 results is very dependent on the examiner and the 363 parameters of the ultrasound device, the evaluation of 364 echogenicity as a criterion for renal pathology was 365 deliberately omitted. ¶ 366 hat gelöscht: / 367 hat gelöscht: / 368 hat gelöscht: On one side this may be explaine hat gelöscht: did 498 hat gelöscht: not reach 499 hat gelöscht: ary 500 hat gelöscht: nce 501 hat gelöscht: 502 hat gelöscht: . ¶ 503 On the other hand, an oral load testing with oxalate rich 504 food was not feasible in this patient group as stool 505 disturbances might occur causing an exacerbation of a fragile 506 system, 507 hat gelöscht: It is well known that urinary oxalate 508 excretion varies with dietary intake. Therefore, Dill et al. 509 established standardised testing protocols which help to 510 discriminate a normal excretion from pathologically high 511 renal elimination after oral oxalate load 38 . In our study we 512 did not evaluate the dietary oxalate intake at the day of 513 urine sampling or the day before. This might had an impact 514 on the results.